EVALUASI PELAKSANAAN DIKLATPIM TK. II. ANGKATAN KE II TAHUN 2004 DI KABUPATEN KARANGANYAR SEBAGAI UPAYA PENINGKATAN KUALITAS SUMBERDAYA MANUSIA - , TJUK SUSILO, Dr. Ely Susanto, MBA. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
District Karanganyar realized that in the face of the era of global the role of human resources in this PNS very strategic , to it hence regional government district Karanganyar everlastingly develop profesionalisme with increase knowledge nor deftness his PNS by means of between others carry out education and exercises . To know the extent to which the success of activity education and exercises need to researched . Type of research that we did is research evaluation concerning the implementation of DIKLATPIM of level II in 2004 in the district of Karanganyar . The approach of that is performed in this research is the approach oriented upon the purpose of , data collected by using the method description of in a qualitative manner , data a primer obtained passing observation , interviews and cheklis . Data secondary acquired through study library and the study of documentation . The population in this research is that the entire participants DIKLATPIM of level IV who held by the agency of shortcourse of staffing district Karanganyar. Evaluation this program is exercised to know the level of the success of the program DIKLATPIM of Level IV in 2004 . Are the criteria of evaluation uses are the criteria of the effective of . Effectiveness of anti bullying the convention of program DIKLATPIM of level IV in 2004 viewed from the achievement of a goal and a target with indications the functioning of a component a component of education . a component is that : 1 . participants shortcourse 2 . widyaiswara 3 . the curriculum 4 . managers 5 . the means and infrastructures . From the research result conducted by through a discussion of the fifth components by comparing between the criteria and the data shows that the implementation of fifth the components can be exercised and functioning well , therefore conclusion this research stated that the implementation of DIKLATPIM level IV at 2004 in the district of Karanganyar come to fruition which means the achievement of the aims and the target of Diklatpim of level IV . Of the conclusion research to execution of Diklatpim of level IV at in the District of Karanganyar that is suggested in the years . Are come so as to be done an increase in good the execution of or quantity participant as well as to expand the horizon a participant so as to widyaiswara plus of a college .